PROGNOSIS OF TRAINING EFFECTS BASED ON SOMATIC CHARACTERISTICS AND SPORT RESULT - Mariusz Klimczyk; Agata Klimczyk (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : Researchers and coaches continue to look for the solutions that would contribute to creation of somatic and mobility condition patterns, allowing the players to obtain sport achievements at the highest level. Therefore, the aim of the study was to trace the sport results' impact in the pole vault and the selected somatic parameters of the vaulters of different ages and comparing them with the results of the players reaching the results at the highest level. Material: The study covered 29 vaulters of 17-19 years old age, engaged in the pole vault at "Zawisza Bydgoszcz", "Gwardia" Pila, "Sląsk" Wrocław, TS "Olimpia" Poznan sports clubs, the Centre of the Pole Vault in Gdańsk, as well as 4 top vaulters - two from Germany, one from the UK and one from Poland. The study was carried out in the training and sports competitions conditions in 2005-2009. In the work teaching observation method was used. The research tools were: assessment of physical development and sports outcome, which were carried out within the start period. The statistical methods were used for analysis of the study results. Results : Indicators of physical development were specified, as well as correlated with sport result for each group. The highest (the only statistically significant) indicator with the pole vault at 0.69 level was reported in the sample - the volume thoracic, exhaling (19-year-old vaulters). Conclusions : The group of vaulters, belonging to the "world's finest" is characterized by a higher rate of shoulders than the other studied groups. There seems to be a large influence on sport technique and result in the pole vault belonging to the proportions of the individual somatic parameters and here the relevant connections can be seen.